Перетворення прозорих плівок нанокомпозитів ПС-ПММА-SiO2 від супергідрофобності до супергідрофільності - Sriboonruang, A.; Kumpika, T.; Sroila, W.; Kantarak, E.; Singjai, P.; Thongsuwan, W. (Publishing house "Academperiodika", 2018)
A transparent superhydrophobic nanocoating with high water contact angle (>150∘ ) was successfully prepared by a simple dip coating method. The coating solutions were prepared by the dissolution of polystyrene (PS) and poly(methyl methacrylate) (PMMA) in toluene. Fumed silica (SiO2) was then added to increase the roughness of the coating. The annealing treatment conditions were investigated to optimize the water contact angle. The heat treatment conditions and other factors were studied systematically to optimize the transmission and the contact angle of water on the films. The results have shown that the films increase with the annealing temperature. The superhydrophobicity of films is observed only in PS-consisted films after the annealing at 200 ∘C. The superhydrophobic/superhydrophilic transformation was achieved at the annealing temperature higher than 200 ∘C due to the decay of the polymer into hydrophilic monomers.